2016
DOI: 10.1158/0008-5472.can-16-0029
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Patients with Gastrointestinal Cancers Can Be Predicted by a Surrogate microRNA Signature for Cancer Stem–like Cells Marked by DCLK1 Kinase

Abstract: DCLK1 is a gastrointestinal (GI) tuft cell kinase that has been investigated as a biomarker of cancer stem-like cells in colon and pancreatic cancers. However, its utility as a biomarker may be limited in principle by signal instability and dilution in heterogeneous tumors, where the proliferation of diverse tumor cell lineages obscures the direct measurement of DCLK1 activity. To address this issue, we explored the definition of a microRNA signature as a surrogate biomarker for DCLK1 in cancer stem-like cells… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…DCLK1 is prognostic in colorectal, head and neck, lung and other cancers . To determine if DCLK1 is prognostic in RCC we performed Cox regression and Kaplan–Meier survival analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DCLK1 is prognostic in colorectal, head and neck, lung and other cancers . To determine if DCLK1 is prognostic in RCC we performed Cox regression and Kaplan–Meier survival analyses.…”
Section: Resultsmentioning
confidence: 99%
“…However, despite significant differences in recurrence‐free survival (RFS) associated with total DCLK1 gene expression, Cox regression analysis of overall survival demonstrated no significant difference (Supporting Information Table II). Given these somewhat confounding results, and our previous hypothesis that DCLK1 expression may be more significant in early cancer before the DCLK1+ cell's progeny dilute its signal, we assessed clinical subgroups. In this context, DCLK1 Isoforms 2 or 4 were able to predict reduced OS in patients with low‐grade disease ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, unlike humans, the 5'promoter of mDclk1 gene does not get hypermethylated and silenced during colon carcinogenesis in response to carcinogens or loss of APC function (34)(35)(36). In recent publications, however, this important difference in the isoform(s) being expressed by colonic tumors in humans vs. mouse models has been ignored (36,40), requiring re-evaluation of results reported in these and other articles, published previously. The various mouse and human isoforms of DCLK1 have been given many different names in literature, leading to much confusion in this field, as discussed (9).…”
mentioning
confidence: 99%
“…Since then, 5'promoter of hDCLK1 gene has been reported to be hypermethylated in gastric (38), pancreatic (38), and lung cancers (39). Interpretation of data in light of these important discoveries, has however remained ignored by some investigators, who have published since 2014 in this field (36,40). A link to our comments, regarding inaccurate interpretation of some data published by Westphalen et al (36), is available at http://www.cell.com/cell-stem-cell/ comments/S1934-5909(16)30003-0.…”
mentioning
confidence: 99%
“…Up-regulated expression of DCLK1 was found broadly in solid tumors almost all over the body, including the esophageal cancer [19], pancreatic cancer [20,21], liver cancer [22], CRC [23,24], etc. and is correlated with poor prognosis [25]. The most recent clinical findings identified that elevated DCLK1+ cells in the blood can be used as a novel non-invasive marker for the diagnosis of incidence, relapse and metastasis for CRC [26], liver cancer [27], pancreatic cancer [28] and Barrett's esophagus and esophageal adenocarcinoma [29].…”
Section: Introductionmentioning
confidence: 99%